Hubungan Makna Antarklausa dalam Kalimat Majemuk pada Terjemahan Surah Al-Furqon - Wahyuni, Tri (2016)
This study aimed to describe the conjunction is used to realize the meaning antarklausa relationships in complex sentences on the translation of Surah Al-Furqan, meaning antarklausa identify forms of relationships in complex sentences on the translation of surah Al-Furqan. Data collection techniques used in this research was followed by technical literature see and note. Mechanical log was used to record the data that has been collected. Method of data analysis was conducted using a unified and read many techniques. Relationship meanings contained in Surah Al-Furqan there are thirteen relationship meanings, namely: the relationship and the sum of their markers, as well; relationship resistance marker but, however; marker selection or relationships; relationships marker time ago. When, while, when, then; relationship requirement if the marker; relationships marker that purpose, for, in order; relationship konsesif real marker; causation relationship markers since; relationships as a result of the marker then, until; relationship reality marker while, whereas; relationship explanation as to why, that is, what, about who, how, who; attribute relationship markers are: the relationship of necessity marker inevitable.